Organic carbon and physical-chemical attributes of a soil in the municipality of Paragominas – PA (Research, Society and Development, 2020)
The quality of the soil has instigated more and more research, since the search for a better production is more and more desired. Thus, the characterization of soil quality has become an effective mechanism to define the system's capacity to be viable in the present and in the future. With this, the present work aims to evaluate by chemical and physical means the quality of the soil collected in situ in Paragominas-Pará, in order to verify the results obtained with the accuracy of each method used. Two samples were taken from a soil profile in two horizons, the first with a depth of 0 - 20cm and the second of 20 - 40cm, they were stored in polyethylene bags and transported to the laboratory for physical-chemical analysis. The results obtained in this research expose the importance of the realization of certain field measures, such as the physical and chemical properties of the soil, in its qualitative bias. Therefore, the variables humidity, color, pH, soil fraction and MO content allow the knowledge of the place and the modification processes that occurred there. In this way, they serve as a basis to identify variations of greater impact.